Beyond the ghetto: methamphetamine and the punishment of rural America. - Linnemann, Travis (Kansas State University, 2011)
Since the early 1970s, the United States has grown increasingly reliant on the criminal justice system to manage a wide array of social problems. Aggressive drug control policies and an over-reliance on imprisonment helped produce the world’s largest prison and correctional population, often described as mass imprisonment. Within this context, the study provides an explanatory account of the political, cultural, and social conditions that encourage states like Kansas to pursue methamphetamine as a major public concern, and to a greater degree than other states with relatively higher meth problems. Ultimately, and most important, the study makes a theoretical contribution by demonstrating how meth control efforts, analogous to previous drug control campaigns, extends punitive drug control rationalities to new cultural contexts and social terrains beyond the so-called ghetto of the inner city, thereby reinforcing and extending the logics of mass imprisonment.
Keywords: Social control; Punishment; Methamphetamine; Rural; Mass imprisonment; Kansas; Sociology (0626)